Development and Training on Implementation of Marketing Website and Financial Reports for UMKM Dapur Kynan: Development and Training on Implementation of Marketing Website and Financial Reports for UMKM Dapur Kynan Pengembangan dan Pelatihan Implementasi Website Pemasaran dan Laporan Keuangan UMKM Dapur Kynan - Fadlillah, Hadyan Mardhi; Prananingrum, Lely; Himawati, Ditya; Lasminiasih; Agustin, Sri Kurniasih (Universitas Lancang Kuning, 2025)
Dapur Kynan is a potential MSME seen from the variety of products and also the complete legality of its business. However, the business being run is experiencing problems, including the difficulty of penetrating a wider market, due to traditional marketing methods such as placing banners, Whatsapp statuses, and from person to person. These MSMEs also experience problems regarding the preparation of financial reports where the records of business transactions and household finances are not yet separated, the records made are still very simple so it is difficult to evaluate the success of the business. The aim of this community service activity is to solve the problems faced by Dapur Kynan by implementing a website as a marketing tool and also a simple bookkeeping application that is integrated with the system. The method we use has 4 stages, namely, data collection and problem analysis, application creation, training preparation, implementation of empowerment through the implementation of the website. The results of this activity show the successful implementation of the website as it makes the process of promotion, sales, and the making of financial reports become easier and more efficient.